Determinants of poultry meat supply in Mexico from 1994 to 2021: importance of technological development and feed grain prices - Nochebuena-Molina, Álvaro; García-Salazar, José Alberto; González-Estrada, Elizabeth; López-Reyna, Ma. del Carmen (Acta Universitaria, 2023)
The generation of value and jobs in the production of poultry meat production in Mexico makes it important to recognize the factors that determine its growth. The objective was to analyze the supply of this meat to identify the variables that have determined its growth in recent years. Time series from 1994 to 2021 were used to estimate a regression model of poultry meat supply. Results indicate that technological progress explains 104.9% of the growth observed in the production of this meat in the period of analysis. The decrease in feed grains prices favored the growth of production by only 1.79%; however, this trend could be reversed in the future since our country’s food dependence on grains determines that international changes could provoke an increase in prices. Due to the probable increase in the price of grains, it is advisable to seek growth through technological progress.